Co-Production of Care During COVID-19. (November 2020) - Andersen, Ditte; Kirkegaard, Sine; Toubøl, Jonas; Carlsen, Hjalmar Bang
This feature article explores how Danish authorities have worked to secure public health in cooperation with citizens, companies, and civil society organizations amid an unfolding pandemic.